Smart Grid Economic Dispatch. (2016) - Dulău, Lucian Ioan; Abrudean, Mihail; Bică, Dorin
Abstract: This paper describes a smart grid economic dispatch (SGED) approach without considering the network equality security constraints. The economic dispatch (ED) problem is one of the fundamental problems in the power system. The objective of ED is to reduce the total power generation cost. The SGED is performed for a test system that comprises three generators and one battery storage device (a 5 MW hydrogen storage unit), considering the consumer power demand. The economic dispatch will be performed for the whole day. The economic dispatch is performed according to the ascending power production cost.